CONVERSATIONAL STYLE AND PREFERENCE STRUCTURE EMPLOYED BY THE HOST AND FOREIGN GUESTS IN ‘SARAH SECHAN’ TALK SHOW NET.TV - WULANDARI, YENI (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Conversational style, High-involvement, High-considerateness, Preference Structure, ‘Sarah Sechan’.People have their own way or style in doing conversation. Through conversation, people also may represent a social action. A person usually tends to accept one thing and refuse the other ones; this structure is called as preference. This study was conducted to find out the conversational styles that are used by the host and foreign guests in ‘Sarah Sechan’ talk show NET. TV, and also to find out kinds of preference structure in the talk show.This study used qualitative approach to gather and analyze the data. The data of this study were spoken words or sentences from three videos of ‘Sarah Sechan’ talk show NET. TV entitled ‘ERU Ingin Mengadakan Konser Kecil di Korea untuk Orang Indonesia di Sana’, ‘Sarah Sechan Kedatangan Angie Miller Juara 3 American Idol’, and ‘Sarah Sechan Kedatangan Finalis Asia Next Top Model’. The videos were downloaded from www.youtube.com.The result of this study shows that the host uses high-involvement style in guiding the talk show. Host’s conversational style in guiding the talk show is to enhance the communication when she talked with a less active guest and also to show her enthusiasm and interest in the topic of conversation or the guests’ talk. Moreover, 4 out of 5 guests in the show also use high-involvement style while one of them uses high-considerateness style. Guests’ high-involvement style in the show is to convey their interest in the conversation. The writer also found when some high-involvement users come in a place and have a conversation; there will be a speaker who unexpectedly becomes less active. Meanwhile, highconsiderateness style in the show happens because the speaker tends to wait the other to finish talking before he takes his turn. The preference structures which are often used in ‘Sarah Sechan’ talk show NET. TV are assessments, requests, and invitations. The responses are negative (dispreferred) and positive (preferred). There are also many kinds of ways in giving responses; given directly, delayed ‘yes’, and given through an action.The writer suggests the next researchers to use different objects in the form of conversation and use another theory of conversational style and preference structure.